Sistem Pendukung Keputusan Penerima Bantuan Program Bina Lingkungan Menggunakan Kombinasi Metode SAW dan SMART - Risdayanti, Monica; Irawan, Muhammad Dedi (Ma'soem University, 2025)
Telkom Regional 1 Sumatra, as a unit of PT. Telkom Indonesia (Persero) Tbk—a state-owned enterprise (SOE)—provides a Community Development Program aimed at improving the welfare of the community. However, the selection process for aid recipients faces obstacles due to the large number of prospective recipients and the variety of their conditions. This study aims to design a Decision Support System (DSS) to determine the recipients of the Community Development Program assistance by combining two methods, namely SAW and SMART. The SAW method is used to calculate the total score of each prospective recipient, while the SMART method serves to determine the weight and ranking of attributes that are considered important in determining the recipients of assistance. With the combination of these two methods, the system can assess and select prospective recipients who best meet the established criteria. This system was developed using a waterfall model, which includes the stages of analysis, design, implementation, and testing. The results of this research are in the form of a DSS prototype that is expected to improve efficiency and accuracy in the process of determining aid recipients, thereby supporting Telkom Regional 1 Sumatra in distributing aid more fairly and effectively.